Histological Study of the Digestive Tract of Liza abu (Heckel) 1-Esophagus - Hussain, Hanan R.D.; Abid, Wijdan B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study includes histological structure of  digestive tract of  Liza abu , Anatomical results found that the digestive tract occupied the largest part of  abdominal cavity ,  the mean gut length was (45.5) cm and relative gut length was (2.9) .  esophagus was a muscular tube length (1.5) cm , esophagus wall containing longitudinal  straight unbranched folds numbering (9) . Histological study  results found that the esophagus composed of four tunica : mucosa , submucosa , muscularis and serosa . The results found that the mucosa consists of three layers : epithelium , lamina propria and muscularis mucosa . The epithelial layer was stratified squamous epithelium thickness (139.1) Âµ containing big size mucous cells strongly staining with PAS and AB .Lamina propria under epithelial tissue thickness(148.3) Âµ composed of irregular dense connective tissue and does not contain esophageal glands .  Muscularis mucosa composed of smooth muscle fibers thickness(10) Âµ.   Submucosa was irregular dense connective tissue enriched with blood capillaries thickness(30)  Âµ .       Tunica muscularis composed of bundles of stri ated skeletal muscle fibers thickness(220.5) Âµ  arranged in two layers internal  longitudinal layer  thickness(73.5) Âµ  and external circular layer thickness  (147) Âµ . Serosa was thin layer of loose connective tissue thickness (21) Âµ .